PENGELOLAAN LINGKUNGAN BELAJAR DAN DAMPAKNYA TERHADAP PERILAKU SISWA SEKOLAH DASAR - Theona, Valentina Putri; Tesalonika, Claudia Jennifer; Marmoah, Sri (Universitas Tanjungpura, 2026)
This article aims to discuss learning environment management and its impact on elementary school students' behavior. The method used is SLR (Systematic Literature Review) by reviewing literature from Google Scholar over the past ten years (2015-2025) and analyzing six articles as the core of the discussion. The results of this study indicate that learning environment management needs to be considered by teachers and parents so that students can achieve positive changes in their learning outcomes. The learning environment affects children's learning outcomes, making it an important factor in their learning success. Without role models or the involvement of various parties, such as parents and teachers, this can create obstacles in managing the learning environment, which will also affect the behavior of elementary school children. Aspects such as habitual behavior patterns in the family will also influence children's attitudes and character. Therefore, teachers and families have an important role in managing a safe and comfortable learning environment that can shape good behavior in elementary school students in preparation for their future.